(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
In order to solve the multi-objective 0/1 knapsack problem, multi-target evolution algorithms often use repair strategies to satisfy capacity limitations. In this paper, two different weighted maintenance strategies based on backpack capacity and capacity limit are proposed to consider the different effects of items on various backpacks. The degree of violation applies to the classic Strength pareto evolutionary algorithm 2 (SPEA2). Experimental results on standard Multi-Objective Knapsack Problem MOKP test problems show that the SPEA2 algorithm using this repair strategy can more effectively converge to the Pareto Optimum Limit.